Anaphylatoxins Activate Ca2+, Akt/PI3-Kinase, and FOXO1/FoxP3 in the Retinal Pigment Epithelium - Busch, Catharina; Annamalai, Balasubramaniam; Abdusalamova, Khava; Reichhart, Nadine; Huber, Christian; Lin, Yuchen; Jo, Emeraldo A. H.; Zipfel, Peter F.; Skerka, Christine; Wildner, Gerhild; Diedrichs-Möhring, Maria; Rohrer, Bärbel; et al. (Frontiers in Immunology, 2017)
Purpose: The retinal pigment epithelium (RPE) is a main target for complement activation in age-related macular degeneration. The anaphylatoxins C3a and C5a, have been thought to mostly play a role as chemoattractants for macrophages and immune cells; here we explore whether they trigger RPE alterations. Specifically, we investigated the RPE as a potential immunoregulatory gate, allowing for active changes in the RPE microenvironment in response to complement. Design: in vitro and in vivo analysis of signaling pathways. Methods: Individual activities of and interaction between the two anaphylatoxin-receptors were tested in cultured RPE cells by fluorescence microscopy, western-blot immunohistochemistry. Main outcome measures: Intracellular free calcium, protein phosphorylation, immunostaining of tissues/cells, multiplex secretion assay. Results: Similar to immune cells, anaphylatoxin exposure resulted in increases in free cytosolic Ca2+, PI3-kinase/Akt activation, FoxP3 and FOXO1 phosphorylation and cytokine/chemokine secretion. Differential responses were elicited depending on whether C3a and C5a were co-administered or applied consecutively; and response amplitudes in co-administration experiments ranged from additive, to driven by C5a (C3a+C5a=C5a) or being smaller than those elicited by C3a alone (C3a+C5a<C3a). Conclusions: We suggest that this combination of integrative signaling between C3aR and C5aR helps the RPE to precisely adopt its immune regulatory function. This data further contributes to our understanding of AMD pathophysiology.